Applying a CRESH aggregate labour index to generate age-wage profiles. Issue 1 (2nd January 2016) - Guest, Ross; Jensen, Bjarne S.
Abstract: This article shows how a CRESH (Constant Ratios of Elasticity of Substitution, Homothetic) labour index can generate more realistic optimal wage profiles than traditional (restrictive) functional forms. The CRESH index function allows for age-specific elasticities of substitution that are implied by a proper choice of CRESH parameters. The ability to generate plausible optimal age-wage profiles can be useful in, for example, calibrating demographic macroeconomic models. The CRESH analysis also provides one explanation for the well-established divergence of actual relative wages by age from the relative age-specific intensity parameters of a simple additive labour index. Moreover, CRESH labour index may explain the increasing relative wages for middle-aged workers as a result of employing larger numbers of older workers (population aging).